1998
DOI: 10.1093/clinchem/44.6.1198
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiac troponin subunit release into serum after acute myocardial infarction and comparison of assays for troponin T and I

Abstract: We examined the release of cardiac troponin T (cTnT) and I (cTnI) into the blood of patients after acute myocardial infarction (AMI). Three postAMI serum samples were applied in separate analytical runs onto a calibrated gel filtration column (Sephacryl S-200), and the proteins were separated by molecular weight. Using commercial cTnT and cTnI assays measured on collected fractions, we found that troponin was released into blood as a ternary complex of cTnT-I-C, a binary complex of cTnI-C, and free cTnT, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
117
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 352 publications
(123 citation statements)
references
References 19 publications
0
117
0
6
Order By: Relevance
“…However, to some degree this may not be realistic in the evaluation of pathologic conditions because cTnI could form complexes with other molecules which interfere with the validity . The cTnI molecules are released into blood as a ternary complex of cTnT‐I‐C, a binary complex of cTnI‐C, and free cTnI in people with myocardial injury, with the binary cTnI‐C complex being the predominant form . More extensive studies are necessary to determine circulating forms of cTnI after myocardial injury in goats.…”
Section: Discussionmentioning
confidence: 99%
“…However, to some degree this may not be realistic in the evaluation of pathologic conditions because cTnI could form complexes with other molecules which interfere with the validity . The cTnI molecules are released into blood as a ternary complex of cTnT‐I‐C, a binary complex of cTnI‐C, and free cTnI in people with myocardial injury, with the binary cTnI‐C complex being the predominant form . More extensive studies are necessary to determine circulating forms of cTnI after myocardial injury in goats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented that rapid modifications of cTnI, depending to some degree on complex interactions with cardiac troponin C and T, occur due to degradation or phosphorylation, which may affect binding of antibodies to the targeted epitope . In contrast to several other assays, the ADVIA Centaur CP TnI‐ultra assay has been reported to recognize free cTnI, cTnI‐T‐C, and binary cTnI‐TnC forms equally well, the latter of which is the main form released into the blood in people with cardiac injury . The degree and type of modification, and the most frequent form of cTnI released in dogs and cats are not known, but the presence of variable modified forms may be a cause of varying antibody affinity.…”
Section: Discussionmentioning
confidence: 99%
“…Free cTnT was released initially, followed by the ternary troponin T/I/C complex, with a small amount of free TnT. 128 Fractionation of cTnI from the plasma of patients with AMI was performed using combinations of 15 monoclonal antibodies directed against various domains of the cTnI molecule. 72 This showed that the dominant form of cTnI released was the cTnI/TnC complex.…”
Section: Cardiac Troponinsmentioning
confidence: 99%